Factors affecting employee engagement among employees at AEON Ipoh Station 18, Perak / Mohammad Hazwan Tarmizi - Tarmizi, Mohammad Hazwan (2016)
This research explores the relationship and influences between human resource practices and employee engagement in AEON lpoh Station 18, Perak. Independent variables include training and development, performance appraisal, work life balance and reward and benefits. The dependent variable is employee engagement. The theoretical framework was developed to show the relationship between independent variables and dependent variable. Four hypotheses were also developed to verify the relationship and influence of the variables. It also shows that, hypotheses 1 and 3 is rejected, while the rest are accepted. The research sample was drawn from the employees of AEON lpoh Station 18, Perak. The questionnaires were distributed to 108 respondents and only 97 sets of questionnaires return back to the researcher. The data collected through questionnaires and were analyzed using Statistical Package for Social Science (SPSS). The findings of this study show that performance appraisal (sig .000) and reward and benefits (sig .000) have significant relationship with employee engagement. Several strategies have been recommended to the organization in order to improve employee engagement among their workers.